Marha legelő növényzetének vizsgálata az Ipoly völgyi Dejtári legelőkön - Turcsányi-Járdi, Ildikó; Penksza, Károly; Saláta-Falusi, Eszter (Gyepgazdálkodási Közlemények, 2022)
The most natural and appropriate way to preserve the biodiversity of grasslands is the utilization, which is confirmed by current research. Conservation management requires intensive cooperation between nature conservation and intensive grassland utilization. Therefore, we investigated the effect of extensive grassland utilization on the outskirts of Dejtár.